Development of various curing effect of nominal strength Geopolymer concrete - S. Kumaravel (Journal of Engineering Science and Technology Review, 2014)
Geopolymer concrete is an innovative method and is produced by complete elimination of ordinary Portland cement byproduced in fly ash. This study on different condition of curing in geopolymer concrete suitable for curing at ambient and heat-cured condition of temperature will widen its application to concrete structures. Low lime fly ash is used as the base material, which is reacted by alkaline solution and additional use of ground granulated blast furnace slag. Workability of fresh concrete and compressive strength of geopolymer concrete was investigated. The curing effect of geopolymer concrete is steam, hot air and ambient cubes specimens are tested in different days. Results are compared for various curing and strength of concrete.